2023
DOI: 10.1039/d3nr03797e
|View full text |Cite
|
Sign up to set email alerts
|

Selective and controlled H2 generation upon additive-free HCOOH dehydrogenation over a Pd/NCS nanocatalyst

Qing Zhang,
Yanlan Wang,
Xiaotao Jin
et al.

Abstract: N-doped carbon nanosphere-stabilized Pd nanoparticles (Pd/NCSs) have been synthesized as high-efficiency nano-catalysts for selective and controlled H2 generation upon additive-free HCOOH dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…To solve the problem above, ammonia borane (NH 3 BH 3 ) is recently expected to be a safe hydrogen storage material for efficient H 2 production, because of its low molecular weight, excellent water solubility, superhigh hydrogen content (19.6 wt %), high stability, uninflammability, and environmental friendliness. Although a range of noble metal catalysts, including Ru, Rh, Pd, Pt, and Au, have been developed for efficient H 2 generation upon NH 3 BH 3 hydrolysis at room temperature (eq ), there is a highly urgent need for exploring the earth-abundant metal nanocatalysts in H 2 generation upon NH 3 BH 3 hydrolysis. As part of our ongoing research, , herein, we have reported a NaBH 4 reduction strategy to boost the catalytic performance of NiMoO 4 nanorods in H 2 generation upon NH 3 BH 3 hydrolysis. In particular, NiMoO 4 has attracted wide attention due to its low cost, fascinating electronic band structure, narrow band gap (2.5–2.9 eV), high surface area, excellent chemical/thermal stability, and environmental friendliness .…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem above, ammonia borane (NH 3 BH 3 ) is recently expected to be a safe hydrogen storage material for efficient H 2 production, because of its low molecular weight, excellent water solubility, superhigh hydrogen content (19.6 wt %), high stability, uninflammability, and environmental friendliness. Although a range of noble metal catalysts, including Ru, Rh, Pd, Pt, and Au, have been developed for efficient H 2 generation upon NH 3 BH 3 hydrolysis at room temperature (eq ), there is a highly urgent need for exploring the earth-abundant metal nanocatalysts in H 2 generation upon NH 3 BH 3 hydrolysis. As part of our ongoing research, , herein, we have reported a NaBH 4 reduction strategy to boost the catalytic performance of NiMoO 4 nanorods in H 2 generation upon NH 3 BH 3 hydrolysis. In particular, NiMoO 4 has attracted wide attention due to its low cost, fascinating electronic band structure, narrow band gap (2.5–2.9 eV), high surface area, excellent chemical/thermal stability, and environmental friendliness .…”
Section: Introductionmentioning
confidence: 99%